Gaps between theory and practice in hemodialysis education during nursing training: : nurses' perception (Revista Brasileira Multidisciplinar, 2026)
Hemodialysis is the main treatment modality in Renal Replacement Therapy, and a qualified multidisciplinary team is required to provide the necessary care to patients. Nursing professionals are key players in this process, as they are present in all phases of dialysis. Despite this, it is possible to identify in the literature that knowledge in hemodialysis is often complemented in practice, highlighting gaps in theoretical teaching. The objective of this study was to analyze the perception of nurses about the gaps in hemodialysis teaching during undergraduate courses. This is a qualitative field study carried out at the Hospital Regional Doutor Cleodon Carlos de Andrade, located in the city of Pau dos Ferros - RN, with nurses. The inclusion criterion was professionals who agreed to participate in the research, regardless of their employment relationship, specialty and sector in which they work, applying an open questionnaire created by the author. The research used Bardin's Content Analysis for an in-depth analysis of the data, following the steps of pre-analysis, exploration of the material and treatment of the results. Six nursing professionals participated in the study, and 15 codes were selected, resulting in three categories: Variety of experience; Lack of technical knowledge; and Suggestions for Teaching in Hemodialysis. The research revealed a gap in the training of hemodialysis nurses, with mostINTRODUCTION: Hemodialysis is the main treatment modality in Renal Replacement Therapy, requiring a qualified multidisciplinary team to provide necessary care to patients. The nursing professional is a key player in this process, as they are present in all phases of dialysis. Despite this, it is possible to identify in the literature that knowledge in hemodialysis is often complemented in practice, highlighting gaps in theoretical teaching. OBJECTIVE: To analyze the perception of nurses about the gaps in hemodialysis education during their undergraduate studies. METHODOLOGY: This is a qualitative, field study conducted at Hospital Regional Doutor Cleodon Carlos de Andrade, located in the municipality of Pau dos Ferros - RN, with nurses. The inclusion criteria were professionals who agreed to participate in the research, regardless of their employment status, specialty, or department. The exclusion criteria were nurses who did not agree to participate in the research, professionals absent on the date of the research, or those on medical leave/vacation. An open-ended questionnaire created by the author was used. The research used Bardin's Content Analysis for an in-depth data analysis, following the stages of pre-analysis, material exploration, and results treatment. RESULTS: Six nursing professionals participated in the study, where 15 codes were selected, leading to the emergence of 3 categories: Variety of experience; Lack of technical knowledge; and Suggestions for Hemodialysis Education. The research revealed a gap in the training of nurses in hemodialysis, with most participants reporting limited practical experience during their undergraduate studies. CONCLUSION: The need for greater clinical practice and continuous updating was emphasized by the professionals, indicating the need for curriculum updates in nursing.
Keywords: Nursing; Hemodialysis; Graduation.